Career Women's Interest in Using Financial Technology - Yati Ria Jessika; Martha Suhardiyah; Soffia Pudji Estiasih; Retno Adilah Saraswati; Luke Suciyati Amna (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to assess the factors influencing the interest of career women in Sidoarjo Regency, East Java, in implementing Financial Technology (Fintech A). In the context of evolving Fintech trends within the community, the study employs a non-probability sampling method, specifically an incidental approach, to select 100 career women respondents from the Krian Sidoarjo community. The data collection process involved administering questionnaires to gauge women's interest in using Fintech, focusing on four key aspects: convenience, perceived benefits, trust, and the comprehensiveness of service features. The data was subsequently subjected to multiple linear regression analyses. According to the results, the amount of trust in the technology, the benefits supplied, the convenience of use, and the quantity of service features offered by Fintech A have a major impact on career women's interest in using Fintech services. According to the research, these are the most important reasons why working women in Sidoarjo Regency are using financial technology. This research contributes to the understanding of user preferences in the Fintech sector, postulating esteemed discernments for Fintech companies looking to tailor their services to encounter the specific requirements and expectations of career-oriented female users in the region.